Mining - Wassim Zuhair Alsindi; Laura Lotti (Internet Policy Review, 2021)
In the context of blockchain networks, mining describes a permissionless process intended to ensure the global consistency of a decentralised ledger. Mining requires the consumption of a costly computational resource to participate in a probabilistic competition that confers specific privileges to a node. These privileges typically relate to the proposal of a new block, including the identity and order of transactions contained within. Mining is incentivised via an algorithmically regulated provision of rewards, usually in the form of newly generated coins and/or transaction fees.
Keywords: 300; Blockchain